English Communication and Meeting Etiquette Training to Enhance the Professionalism of Public Administration Students: Pelatihan English Communication dan Meeting Etiquette untuk Meningkatkan Profesionalisme Mahasiswa Administrasi Publik - Yulia Wiji Astika; Teta Wismar; Iin Nirwana; Monalisa Monalisa (Room of Civil Society Development, 2026)
Workplace developments and increasing demands for professionalism in public service require students to develop strong communication skills, including the ability to communicate in English and apply professional meeting etiquette. However, some students still face challenges in oral communication, self-confidence, and the application of communication etiquette in professional settings. This community service program aimed to enhance students’ capacity through English Communication and Meeting Etiquette training to support professionalism in public service. The program involved 30 Public Administration students and was implemented using an experiential learning approach through material delivery, meeting simulations, public service communication practice, mentoring, and evaluation. Evaluation was conducted through pre-tests, post-tests, and skill observations. Based on the activity evaluation recap, the participants’ average score increased from 61 in the pre-test to 85 in the post-test. Observation results also indicated improvements in speaking skills, presentation skills, self-confidence, and the application of professional meeting etiquette. These results suggest that English Communication and Meeting Etiquette training contributes positively to improving students’ professional communication skills in supporting high-quality and responsive public service.